2016
DOI: 10.1182/blood-2015-08-664995
|View full text |Cite
|
Sign up to set email alerts
|

ICAM-1–expressing neutrophils exhibit enhanced effector functions in murine models of endotoxemia

Abstract: Key Points Murine neutrophils can be stimulated by LPS to express de novo ICAM-1 in vitro and in murine models of endotoxemia in vivo. Neutrophil ICAM-1 expression correlated with enhanced phagocytosis and ROS generation, and ICAM-1 deficiency caused defective phagocytosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
110
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(123 citation statements)
references
References 71 publications
13
110
0
Order By: Relevance
“…For example, CXCR4 expression is increased in aged or senescent neutrophils and is associated with neutrophil trafficking [43]. Recently, ICAM-1 + phenotype of neutrophils was identified following stimulation of the neutrophils with LPS, TNF and zymogen particles in vitro , and these neutrophils were shown to exhibit increased effector functions in terms of exaggerated ROS production and phagocytosis [25]. In the current study, using a clinically relevant model of sepsis in mice, we identified increased levels of ICAM-1 + neutrophils in the blood as well as in lungs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, CXCR4 expression is increased in aged or senescent neutrophils and is associated with neutrophil trafficking [43]. Recently, ICAM-1 + phenotype of neutrophils was identified following stimulation of the neutrophils with LPS, TNF and zymogen particles in vitro , and these neutrophils were shown to exhibit increased effector functions in terms of exaggerated ROS production and phagocytosis [25]. In the current study, using a clinically relevant model of sepsis in mice, we identified increased levels of ICAM-1 + neutrophils in the blood as well as in lungs.…”
Section: Discussionmentioning
confidence: 99%
“…An increased expression of ICAM-1 on neutrophils after stimulation with LPS and TNF-α has been shown, which resulted in significant increases in neutrophil-neutrophil adherence and aggregation [24]. The ICAM-1 expressing neutrophils were shown to enhance the effector functions through the increase of phagocytosis and ROS generation [25]. The role of this subset of neutrophils in terms of augmenting inflammation and tissue injury in a clinically relevant model of systemic inflammation has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13][14] In the peripheral blood, heterogeneity of neutrophils arises from ageing of circulating neutrophils and the concomitant release of nonaged neutrophils from the bone marrow: in a microbiotadriven process, ageing neutrophils gradually upregulate the chemokine receptor CXCR4 on their cell surface during intravascular margination in peripheral organs, which allows the clearance of these leukocytes in bone marrow, liver, and spleen via the chemokine CXCL12/SDF-1a. 17,[36][37][38][39] These events promote an IL-17/granulocyte colony-stimulating factor-mediated feedback inhibition of neutrophil production in the bone marrow and cause the rhythmic modulation of the hematopoietic stem cell niche in the steady state.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7][8] Although neutrophils have originally been considered to be a homogenous population of blood cells, recent studies point to the existence of different phenotypes of these leukocytes. [9][10][11][12][13][14] In this context, neutrophils aged in the circulation seem to be of particular relevance because these immune cells are critically involved in the mobilization of nonaged neutrophils from the bone marrow under steady-state conditions [15][16][17] : in a microbiota-driven process, 18 ageing neutrophils upregulate the chemokine receptor CXCR4 on their cell surface, which allows them to home back to the bone marrow (via the chemokine CXCL12), ultimately resulting in the clearance of these leukocytes by resident macrophages. 19 In a negativefeedback mechanism, these events regulate granulopoiesis through the interleukin-17 (IL-17)/granulocyte colony-stimulating factor axis.…”
Section: Introductionmentioning
confidence: 99%